(untitled) (REMUNOM, 2024)
Feedlot beef cattle production has become a common practice in Brazilian livestock farming due to the increasing demand for meat and the intensification of production. However, this practice has raised challenges related to nutritional metabolic diseases, such as ruminal acidosis, ketosis, bloat, and hepatic lipidosis, which negatively affect the animals’ health and performance. This article aims to explore the main causes of these diseases, their impacts on productivity and the livestock economy, and the nutritional management strategies to prevent them. The research was conducted through a bibliographic review, analyzing recent studies on the subject. The results indicate that adopting proper nutritional management, with balanced diets and continuous animal health monitoring, is essential to minimize the risks of these diseases and ensure productive efficiency in feedlot systems.